Exploring the global prevalence of mood and anxiety disorders in LGBTIQ+ people: A systematic review - Johnson, Sarah; Bogdanova, Mariia; Alexander, Laith; Stokes, Paul R. A. (Frontiers in Psychiatry, 2025)
BackgroundThe prevalence of mood and anxiety disorders in LGBTIQ+ individuals (lesbian, gay, bisexual, transgender, intersex, queer, and other sexual/gender minorities) is not well understood. Studies suggest that LGBTIQ+ people may have higher rates of mood and anxiety disorders, potentially influenced by societal acceptance.AimsThis systematic review aims to examine the prevalence of depressive disorders (DD), bipolar disorders (BD), and anxiety disorders in LGBTIQ+ populations and explore potential associations with societal acceptance in different global regions.MethodsA systematic search of PubMed, Embase, APA PsychInfo, and citations from 1990–2022 identified studies reporting on the prevalence of DD, BD, and anxiety disorders among LGBTIQ+ people. These rates were compared to societal acceptance, using the Williams’ Institute Global Acceptance Index, and to general population rates. Study quality was assessed with the National Institute of Health checklist.Results123 studies from 31 countries were included, with 116 rated as good quality. Individual study sample sizes ranged from 15 to over 254,462,596. Mean prevalence rates in LGBTIQ+ populations from these studies was 35.3% for depressive disorders, 5.6% for bipolar disorders, and 34.3% for anxiety disorders. A significant correlation was found between societal acceptance and depressive and anxiety disorder prevalence rates in North American LGBTIQ+ populations.ConclusionsThis study found that LGBTIQ+ people experience markedly higher rates of mood and anxiety disorders compared to the general population, with societal acceptance correlating with these rates in North America. Further research is needed, particularly for underrepresented groups such as nonbinary individuals and those identifying as pansexual, asexual, or genderqueer.Systematic review registrationwww.crd.york.ac.uk/prospero/, identifier CRD42022320324.